Preparation and characterization of PVC-LiClO4 based composite polymer electrolyte - Ahmad A.; Rahman M.Y.A.; Su'ait M.S. (2023)
The preparation of PVC-LiClO4 based composite polymer electrolyte was carried out to study the effect of ceramic fillers such as ZnO, TiO2 and Al2O3 on the room temperature conductivity. The samples were tested using impedance spectroscopy, differential scanning calorimetry (DSC), thermogravimetric analysis (TGA) and scanning electron microscopy (SEM). The samples were prepared with different percentage (%) by weight of ceramic filler. The highest ionic conductivity achieved was 3.710-7 S cm-1 for the sample prepared with 20% of ZnO. The glass transition temperature decreases with the fillers concentration due to the increasing amorphous state. While, the decomposition temperature increases with the increase in the fillers content. Both of these thermal properties influence the enhancement of the conductivity value. The morphology of the samples shows the even distribution of the ceramic filler in the samples however the filler starts to agglomerate in the sample at higher concentration of filler. In conclusion, the addition of ceramic filler improves the ionic conductivity of PVC-LiCIO4 composite polymer electrolyte. 2008 Elsevier B.V. All rights reserved.